Penetapan Kadar Omega-3 Undur-Undur Laut (Emerita emeritus) dalam Bentuk Granul, Bubur, dan Mentah secara Kromatografi Gas - Angelina Desio Lisarni; Endang Sri Rejeki; Suhartinah Suhartinah (Fakultas Farmasi Universitas Setia Budi, 2015)
Mole crab is the coastal of biological resources are spreading quite extensive and has a high nutrient content, especially omega-3 fatty acids are good for memory. Omega-3 fatty acids consist of linolenic acid, EPA, and DHA. Mole crab is processed into a granule and instant baby puree with a variety of cooking and processing. This study aims to compare the levels of omega-3 content of granule and puree that has been cooked with mole crab raw without cooking. Mole crab that was acquired, cleaned and dried and then processed into mole crab raw, the roasted dried granule, the granule sun dried, instant puree with the addition of a mole crab, and the instant puree without addition of mole crab (placebo). Samples are extracted using soxhlet with solvents chloroform:methanol (2:1). Analysis using gas chromatography with Nitrogen gas as phases of motion. The content of omega-3 was calculated based on the relative percent and analyzed by Shapiro wilk test for normality test. The result of the experiment showed that total content of omega (linolenic acid, EPA, and DHA) extract of mole crab raw was 44,416 g/100 g, extract of granuleroasted was 52,280 g/100 g, extract of granule-sundried was 29,489 g/100 g, extract of mole crabpuree and extract of puree as a placebo was not detected of omega-3.